2007
DOI: 10.1530/eje-07-0127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on plasma visfatin and eotaxin levels

Abstract: Objective: Visfatin, a novel adipokine, was revealed to be associated with obesity and to have insulinmimetic effect. Eotaxin, which is an important chemokine in asthma, was recently reported to be associated with obesity in mice and humans. We evaluated the effect of exercise training on plasma visfatin and eotaxin levels in association with cardiovascular risk factors. Design: Forty-eight non-diabetic Korean women were evaluated before and after a 12 week exercise program including aerobic exercise (45 min/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
77
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 32 publications
13
77
0
3
Order By: Relevance
“…Lee et al (2010) reported that after twelve weeks of aerobic training on overweight subjects, there was desirable changes in body composition by reduced visfatin (29). Choi et al (2007) by investigating the effect of 12 weeks of combined endurance and resistance training, observed reduced visfatin (30). Seo et al (2011) also after twelve weeks of combined training on middle-aged women, reported reduced visfatin (31) which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lee et al (2010) reported that after twelve weeks of aerobic training on overweight subjects, there was desirable changes in body composition by reduced visfatin (29). Choi et al (2007) by investigating the effect of 12 weeks of combined endurance and resistance training, observed reduced visfatin (30). Seo et al (2011) also after twelve weeks of combined training on middle-aged women, reported reduced visfatin (31) which is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies did not find any relationship between insulin resistance and visfatin (27,28), while in a study, Lee et al (2010) observed that doing 12 weeks aerobic training significantly reduced visfatin and improved insulin resistance index in obese women (29). On the other hand, no change in the level of plasma visfatin have been reported after aerobic training (30).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, exercise training that resulted in weight loss induced significant reductions in plasma visfatin in young, overweight Korean women (27). Visfatin was also measured in response to acute exercise bouts where visfatin mRNA expression in SAT was found to be elevated threefold in the hours immediately after exercise (28).…”
Section: Discussionmentioning
confidence: 99%
“…In other study PVL among diabetic patients were same after 12 weeks of aerobic, resistance and combined exercises [19]. In contrast, one study has shown that exercise training with weight loss induced a significant reduction of PVL in non-diabetic Korean women [20]. Another research among obese females reported that PVL reduced after 12 weeks of combined training (aerobic-strength), this reduction was associated with a decrease in anthropometric variables and blood glucose levels [21].…”
Section: Introductionmentioning
confidence: 99%